Dead men don't wear plaid [videorecording (DVD)] - Rózsa, Miklós, 1907-1995 (Universal Home Video, 1999)
Private eye Rigby Reardon is hired by a beautiful woman to investigate the mysterious death of her father--a wealthy scientist, philanthropist, and cheesemaker.